PENGARUH FINANCIAL KNOWLEDGE, FINANCIAL ATTITUDE, DAN FINANCIAL LITERACY TERHADAP FINANCIAL MANAGEMENT BEHAVIOR PADA UMKM SEKTOR FASHION KOTA BENGKULU - Indah Parastika; Arifah Hidayati; Idham lakoni (Universitas Triatma Mulya, 2023)
This study examine financial literacy financial attitude and financial knowledge in relation to financial management behavior in Bengkulu city's UMKM fashion industry. This study both quantitative and qualitative data gathering methods, including a questionnaire. The study's sample included 75 respondents. The saturated sample method is the sampling approach that is employed. processing of primary and secondary data utilizing SPSS's multiple regression analysis approach and statistical analysis methods. According to the study's findings, financial management behavior is positively impacted the factors of financial obligations, financial knowledge, and financial attitudes at the same time. Each independent variable influences financial management behavior favorably to some extent.